Analysis of the Quality of the Anahoni River Based on Physical and Biological Parameters - M. Sehol; Kasmawati; Mangesa, Rosita; Irsan, Irsan; Rosmida R Dahlan (PT Inovasi Pratama Internasional, 2025)
This study aims to analyze the quality of the waters of the Anahoni river due to gold mining by covering physical and biological parameters. Physical parameters include color, temperature and TSS (Total Suspended Solids). In the results of measuring the color of the waters of the Anahoni River and Waelata River at all research stations, it ranges from 1 - 5 NTU, which is still below the maximum limit. The results of the water temperature values ​​at the research stations varied between 26.4 – 34.40C. The measured water TSS value at all research stations ranged from 0.011 - 0.018 indicating that the TSS value was below the quality standard value. Biological parameters using coliform bacteria. The results of using fecal coliform bacteria varied at each research station with a range of 0 – 68 MPN/100 mL